The Effects of Calcium Supplement on Serum Lipoprotein in Obese Adults Receiving Energy Restricted Diet - M Shalileh; F Shidfar; SH Eghtesadi; H Haghani; I Heidari (Tehran University of Medical Sciences, 2009)
Background: Coronary heart disease is one of the most important problems of public health. One risk factor is dyslipidemia. Evidence from molecular and animal research and epidemiologic investigations indicate that calcium intake may influence lipid metabolism.But intervention studies have produced conflicting results.Objective of this study was to determine the effects of calcium supplementation on serum lipid profiles in the face of caloric restriction in obese adults. Methods: A double blind randomized placebo-controlled trial on 40 adults with Body Mass Index (BMI)>25kg/m² was conducted in Iran University of Medical Sciences in 2006.Subjects were maintained for 24 weeks on a balanced deficit diet (-500 kcal/d deficit) and randomly assigned to two groups with 1000 mg ca/d as calcium carbonate, or placebo. A General Linear Model was used for the analyses. Results:  There were no significant differences in variables at the 12th and 24th week between the two groups (P> 0.015). But the total cholesterol, LDL-C decreased significantly at the 12th and 24th week in the two groups compared to the initial values (P< 0.05). Ratios of TC/HDL-C,TC/LDL-C and LDL-C/HDL-C decreased significantly at the 12th and 24th week compareddto baseline only in the calcium group (P< 0.05). Similarly, TG and VLDL-C decreased significantly at the 24th week compared to baseline only in the calcium group (P< 0.05). Conclusions: Twenty four weeks of supplementation with 1000 mg ca/d did not have any effect on serum lipoprotein beyond what can be achieved in an energy restricted diet